Politics of Disillusionment: Violence and Idealism in Liam O’Flaherty’s “Civil War” and Frank O’Connor’s “Guests of the Nation” - Pinto, Rodrigo Moreira (ABEI Journal, 2021)
Having their formative years in the period right before the Irish revolution, Liam O’Flaherty and Frank O’Connor were deeply influenced by nationalistic propaganda. Inspired by Republican ideals, both writers-to-be took an active, though modest, role in the War of Independence and in the ensuing Civil War. The literature they produced when the conflicts had ceased, however, displays a very critical and contrasting perspective to the one that had driven them to support the revolution. Analysing the short stories “Civil War” (1924), by Liam O’Flaherty, and “Guests of the Nation” (1932), by Frank O’Connor, this essay explores why and how both authors resorted to stark, gruesome, and nihilistic approaches to the Irish revolutionary period instead of adhering to more romantic and idealistic perspectives.